THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING (TBLT) AND ENGLISH FOR SPECIFIC PURPOSES (ESP) CONTEXT IN SMK MUHAMMADIYAH 1 MALANG - Hima Aninda Nidhommil; Teguh Hadi Saputro (ELITE Association Indonesia, 2019)
The Internal Community Service Program (PPMI) managed by the University of Muhammadiyah Malang was designed and developed to help the partner school, SMK Muhammadiyah 1 Malang to overcome the problems faced by the school. The results of the pre-observation or situation analysis have shown that the school faces a major problem from the aspect of teaching performance of English teachers. To overcome this problem, the project team proposed best practices in teaching English using the Task-Based Language Teaching (TBLT) approach as an innovative teaching approach in the context of English for Specific Purposes (ESP). Furthermore, the results of the preliminary study were used as a reference for the preparation of four learning meetings in each class. In this program, the teachers are shown how to 1. Prepare for teaching and learning process, starting from designing lesson plans including the ESP materials, media and evaluation instruments, 2. Implement the teaching and learning process by using TBLT, 3. Evaluating students. It is hoped that with the methods proposed in this program, the English teachers from the partner school can improve their teaching skills which then have a positive effect on improving the quality of the school in creating a more effective learning environment for students.